Vogler’s Hero’s Journey Representation in Puss in Boots: The Last Wish Film (2022) - Aimee, Mersha Khaifa; Zamruddin, Mardliya Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research examines how the hero's journey is represented through the animated Puss in Boots: The Last Wish film that was released in 2022, using Christopher Vogler's hero's journey theory. Vogler's twelve-stage model is used to trace the development of the main character, Puss, and relate each stage to the conflicts that he experienced throughout the journey. This study uses a qualitative method, and the data taken consist of dialogues and scenes of the film. The results of this study show that the Puss in Boots: The Last Wish film represents and follows Vogler's hero's journey through the character of Puss. In the film, Puss had faced ten stages and passed all of them with a character development that showed his transformation from an arrogant and individualistic person to a wise and appreciative figure. Each stage of the hero's journey not only illustrates Puss's transformation but also shows values about courage, friendship, and appreciation of the meaning of life as messages for the audience.